Capacity for diagnosis and treatment of heart failure in sub-Saharan Africa. Issue 23 (10th May 2017) - Carlson, Selma; Duber, Herbert C; Achan, Jane; Ikilezi, Gloria; Mokdad, Ali H; Stergachis, Andy; Wollum, Alexandra; Bukhman, Gene; Roth, Gregory A
Abstract : Objective: Heart failure is a major cause of disease burden in sub-Saharan Africa (SSA). There is an urgent need for better strategies for heart failure management in this region. However, there is little information on the capacity to diagnose and treat heart failure in SSA. We aim to provide a better understanding of the capacity to diagnose and treat heart failure in Kenya and Uganda to inform policy planning and interventions. Methods: We analysed data from a nationally representative survey of health facilities in Kenya and Uganda (197 health facilities in Uganda and 143 in Kenya). We report on the availability of cardiac diagnostic technologies and select medications for heart failure (β-blockers, ACE inhibitors and furosemide). Facility-level data were analysed by country and platform type (hospital vs ambulatory facilities). Results: Functional and staffed radiography, ultrasound and ECG were available in less than half of hospitals in Kenya and Uganda combined. Of the hospitals surveyed, 49% of Kenyan and 77% of Ugandan hospitals reported availability of the heart failure medication package. ACE inhibitors were only available in 51% of Kenyan and 79% of Ugandan hospitals. Almost one-third of the hospitals in each country had a stock-out of at least one of the medication classes in the prior quarter. Conclusions: Few facilities in Kenya and Uganda were prepared to diagnose and manage heart failure. Medication shortages and stock-outs were common. Our findings call for increased investment in cardiac care to reduce the growing burden of heart failure.